A small molecule inhibitor of HER3: a proof-of-concept study. Issue 17 (10th September 2020) - Colomba, Audrey; Fitzek, Martina; George, Roger; Weitsman, Gregory; Roberts, Selene; Zanetti-Domingues, Laura; Hirsch, Michael; Rolfe, Daniel J.; Mehmood, Shahid; Madin, Andrew; Claus, Jeroen; Kjaer, Svend; et al.
Abstract : Despite being catalytically defective, pseudokinases are typically essential players of cellular signalling, acting as allosteric regulators of their active counterparts. Deregulation of a growing number of pseudokinases has been linked to human diseases, making pseudokinases therapeutic targets of interest. Pseudokinases can be dynamic, adopting specific conformations critical for their allosteric function. Interfering with their allosteric role, with small molecules that would lock pseudokinases in a conformation preventing their productive partner interactions, is an attractive therapeutic strategy to explore. As a well-known allosteric activator of epidermal growth factor receptor family members, and playing a major part in cancer progression, the pseudokinase HER3 is a relevant context in which to address the potential of pseudokinases as drug targets for the development of allosteric inhibitors. In this proof-of-concept study, we developed a multiplex, medium-throughput thermal shift assay screening strategy to assess over 100 000 compounds and identify selective small molecule inhibitors that would trap HER3 in a conformation which is unfavourable for the formation of an active HER2–HER3 heterodimer. As a proof-of-concept compound, AC3573 bound with some specificity to HER3 and abrogated HER2–HER3 complex formation and downstream signalling in cells. Our study highlights the opportunity to identify new molecular mechanisms of action interfering with the biological function of pseudokinases.